Optimization Of Improving Self-Care And Independence In The Elderly With Hypertension Friendly Support - Diana Pefbrianti; M Noor Ifansyah (International Journal Of Community Service, 2025)
The community service partner is the elderly and families in Tambak Baru Ilir Village. There are still many elderly people who suffer from hypertension. If hypertension does not show symptoms, the elderly rarely seek treatment. The elderly rarely engage in physical activity. Individuals with hypertension often experience complex problems such as difficulties in fulfilling self-care and a decline in quality of life, leading to the elderly becoming dependent on others around them. Elderly and families need to be socialized about hypertension-friendly support to address issues caused by hypertension through hypertension education, education about the DASH diet, stress management, and a 60-minute exercise session for 25 elderly individuals. The result of the hypertension-friendly support education is that the elderly and their families feel enthusiastic about this activity. In self-care, all are in the sufficient category and all are in the independent category. Hypertension-friendly support can have a positive impact on elderly individuals who face issues due to hypertension, helping them to maintain their lives and continually respond to their surrounding environment. Keywords: hypertension, DASH diet, stress management, defansive exercise, elderly.